2019
DOI: 10.1155/2019/7395239
|View full text |Cite
|
Sign up to set email alerts
|

Phoenix dactyliferaProtects against Doxorubicin-Induced Cardiotoxicity and Nephrotoxicity

Abstract: Doxorubicin (DOX) is an important anticancer drug used widely in the treatment of leukemia and lymphoma. The suitability of DOX is enhanced by its high therapeutic index, but its potential to cause cardiotoxicity and nephrotoxicity remains a prime concern in anticancer therapeutics. This study is designed to determine the effect of Phoenix dactylifera extract (PDE) on DOX-induced cardiotoxicity and nephrotoxicity. Experimental rats were divided into four groups, receiving normal saline 4 ml/kg, DOX alone, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
5
12
0
Order By: Relevance
“…We found no statistically significant (p > 0:05) changes in the studied electrolytes (Na + , K + , and Cl -), which was also previously reported by other authors in other animal models [22], although others have reported significant changes [23]. At this stage, we have no explanation for why cardiac troponin I (cTnI) levels were not elevated, as its values were <0.20 ng/mL in the control and MXB pretreatment groups as well as in the doxorubicin group.…”
supporting
confidence: 88%
“…We found no statistically significant (p > 0:05) changes in the studied electrolytes (Na + , K + , and Cl -), which was also previously reported by other authors in other animal models [22], although others have reported significant changes [23]. At this stage, we have no explanation for why cardiac troponin I (cTnI) levels were not elevated, as its values were <0.20 ng/mL in the control and MXB pretreatment groups as well as in the doxorubicin group.…”
supporting
confidence: 88%
“…High intakes of sodium have been reported to be associated with an increased risk of cardiovascular disease especially heart disease [57]. Plasma sodium ion was elevated in rats intoxicated with DOX compared with the normal control, and there was observed a decrease in elevated ion to normal values in groups who received processed Cucurbita maxima seed flour as it was also reported previously that elevated sodium ion was seen in rats having cardiac damage [58] Atherogenic index denotes the magnitude of the potential occurrence of atherosclerosis [59]. The higher of atherogenic index, the potential occurrence of atherosclerosis.…”
Section: Discussionsupporting
confidence: 60%
“…They were also found to activate a cellular redox defense mechanism by stimulating endogenous antioxidant fractions [32] and keep the cells from xenobiotic oxidative stress, DNA impairment, and apoptosis [33]. Much attention has been given to using plant chemicals as a defensive strategy to resolve cardiotoxicity triggered by DOX [34][35][36].…”
Section: Introductionmentioning
confidence: 99%